2021
DOI: 10.12911/22998993/133966
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Efficiency of Using Organic Waste from the Brewing Industry for Bioremediation of Oil-Contaminated Soils

Abstract: At present, the development and optimization of methods to eliminate the consequences of soil contamination with hydrocarbons is gaining increasing economic and social importance; it is the basis for sustainable development of the oil industry. Within the frames of the scientific research, a review of literature was carried out in the sphere of utilization of organic wastes from the food industry in reclamation of oil-contaminated soils; an experimental study of efficiency of the use of wastes from the brewing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…The interfacial tension at oil/water interfaces and the surface tension at air/water interfaces are both decreased by these amphiphilic biomolecules. In vitro and field studies have demonstrated that organic brewing waste boosts the activity of enzymes produced by microorganisms that oxidize hydrocarbons, speeds up the reduction of oil content, and enhances the chemical and physical characteristics of chernozemic environments ( Strizhenok et al, 2021 ). BSG includes complexes of nutrients and physiologically active chemicals that support the growth of hydrocarbon oxidizing microorganisms and consequently result in the degradation of hydrocarbons in the soil ecosystem ( Fig.…”
Section: Brewery Waste Prospectivementioning
confidence: 99%
See 1 more Smart Citation
“…The interfacial tension at oil/water interfaces and the surface tension at air/water interfaces are both decreased by these amphiphilic biomolecules. In vitro and field studies have demonstrated that organic brewing waste boosts the activity of enzymes produced by microorganisms that oxidize hydrocarbons, speeds up the reduction of oil content, and enhances the chemical and physical characteristics of chernozemic environments ( Strizhenok et al, 2021 ). BSG includes complexes of nutrients and physiologically active chemicals that support the growth of hydrocarbon oxidizing microorganisms and consequently result in the degradation of hydrocarbons in the soil ecosystem ( Fig.…”
Section: Brewery Waste Prospectivementioning
confidence: 99%
“…BSG includes complexes of nutrients and physiologically active chemicals that support the growth of hydrocarbon oxidizing microorganisms and consequently result in the degradation of hydrocarbons in the soil ecosystem ( Fig. 4 b) ( Strizhenok et al, 2021 ).…”
Section: Brewery Waste Prospectivementioning
confidence: 99%
“…Численность (титр) микроорганизмов-деструкторов органического вещества падает намного ниже в сравнении с незагрязненными участками, а их функциональная активность (метаболизм), связанная с биоразложением, замедляется в шесть раз [14; 15]. Все это влечет за собой усиление процессов эрозии и снижения плодородия и общего здоровья почвенной экосистемы [16][17][18].…”
Section: Introductionunclassified